The Relationship between Strategy and Information Systems and Their Impact on Achieving Sustainable Competitive Advantage in Supply Chain- A Survey Study on Samples from Iraqi Industrial Companies - Bilal .J. Al- Qaysi (International Journal of Supply Chain Management, 2019)
Institutions are accelerating to achieve a sustainable competitive advantage in supply chain, its range is expanding to find the tools to help them achieve this purpose, and the growing need for these organizations to understand their current status as well as their potential. Therefore, organizations always depend on information systems to process transactions, develop products, access a large proportion of their budgets to support their operational and commercial activities, and how to acquire knowledge for business owners to access these investments. Wealth, naturally, includes an assessment of information technology and a link to business success and access to potential assets within existing innovation mechanisms primarily on the strategic emphasis of organizations in particular. The aim of this research is: to discuss the importance of integrating business strategy and information systems in the framework of achieving sustainable competitive advantage in supply chain and its impact on the sustainability of organizations and their endurance in a world of intense competition and rapid change. Design / Methodology / Approach: reviews and discusses existing literature of interrelationship and framing between business strategy, and customer relationship management systems (CRM) for related issues. Conceptual models are presented to clarify the interrelationship and impact between search streams. Results - the research finds a set of most important results is that if business organizations achieve a sustainable competitive advantage in supply chain, this requires them to match their own business strategy and information systems with the use of their resources and information and their compatibility with competitors' resources and capabilities in the context of competitive environment and how to maintain this feature which helps them achieve institutional distinction compared to their competitors. Practical fallouts: The main implications of practical fallouts revolve around the idea that "in today's intense competition markets, organizations must aim to seek sustainable competitive advantage in order to be competitive, and information systems will play a critical role in generating the necessary data that can through which organizations develop and implement business strategy, which in turn promotes the practice of success and achieve superiority at the business level.